Alkaline and acid phosptiatases in different tissues of Channa punctatus exposed to metanil yellow - Sharma, S D; ., Maya (Indian Journal of Fisheries, 2011)
The live specimens of Channa punctatuswere procured from the nearby water bodiesand acclimatized to laboratory conditions(temperature 22°±2°C, pH 6.8, D.O. 7 mg/litre, hardness 6.6 mg/litre, total solids 21.6mg/litre) for one week. Then 80 healthyfishes of weight group 40-60 g were selectedirrespective of their sex and washed with0.1% KMnO^ solution, prior toexperimentation, to avoid any externalinfection. The toxicant metanil yellow, wasused during the present investigation.